Pembuatan Edibel Film sebagai Zat Pemlastik dari Pati Ubi Kayu dengan Penambahan Sorbitol - MF. Sri Mulyaningsih; Ery Fatarina; Ahmad Shobib (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
In the increasing public knowledge about the dangers of plastic packaging that can harm the environment, the use edible film is something very interesting. The advantage of the use of the edible film can protect food products as well as safe from the environment. To produce good quality edible film substance can not be separated from the plasticizer is added. Plasticizer substance is an organic material with low molecular weight are added in the edible film with intent to weaken the stiffness of the polymer, while increasing the flexibility and extensibility of polymer. Edible direct utilization of the film is as a coating material for fruits. In order to improve the utilization of cassava starch we conducted research on “Edible Film as Substitute For Plastic Substances From Cassava Starch With The Addition of Sorbitol “ .From the results of calculations using the statistical program found that the effect of variable starch by -0,1 ; sorbitol at 0,3 ; temperature of -0,15. This means that the most influential variable in making edible film of starch with the addition of sorbitol is it self, followed by the final temperature and starch concentration. Of interaction effect between variables, it was found that the effect of the interaction value of 0,05. It also means that the variable effects of starch and sorbitol also depend on the effect of variable temperatures to get the most edible film. Can be seen also from the normal probability graph effect, that is the furthest point sorbitol, which means these variable are the most influential and has the effect of the interaction between variables